1994
DOI: 10.1111/j.1432-1033.1994.tb19005.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and cDNA cloning of a four‐domain Kazal proteinase inhibitor from crayfish blood cells

Abstract: A cDNA with an open reading frame of 684 base pairs was isolated from a library from blood cells of the crayfish Pacifastacus leniusculus. It codes for a signal sequence and a mature protein of 209 amino acids with a predicted molecular mass of 22.7 kDa. The amino acid sequence consists of four repeated stretches (45-73% identical to each other), indicating that the protein has four domains. The domains have significant sequence similarity to serine proteinase inhibitors of the Kazal family. The three first do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 44 publications
(31 reference statements)
3
45
0
Order By: Relevance
“…The crayfish ferritin was analyzed by native PAGE and SDS/ PAGE under reducing conditions. For determination of the Nterminal sequence, 10 pg ferritin was run on 15% SDSPAGE and then transferred to poly(viny1idene difluoride) membrane (Millipore), as described in Johansson et al (1994). The 20-kDa ferritin band was excised for determination of the N-terminal sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The crayfish ferritin was analyzed by native PAGE and SDS/ PAGE under reducing conditions. For determination of the Nterminal sequence, 10 pg ferritin was run on 15% SDSPAGE and then transferred to poly(viny1idene difluoride) membrane (Millipore), as described in Johansson et al (1994). The 20-kDa ferritin band was excised for determination of the N-terminal sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these genes code for proteins known to be involved in defense reactions, such as VMO-I, MBP, and proteinase inhibitors (1,3,13,15,29), although there is little information available about to which extent, if any, they are effective in an antiviral response. Our experiments have, so far, not indicated that these proteins, with the exception of ALF, have a specific role in reducing viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…The monospecific antiserum was used to screen a crayfish hemocyte cDNA library (23). An Northern Blot Analysis.…”
mentioning
confidence: 99%